The hernia in the postoperative scar – can it be avoided? - Tobiasz, Michał; Turkosz, Agnieszka; Smorąg, Mateusz; Tobiasz, Maciej; Polski, Paweł (Journal of Education, Health and Sport, 2019)
The surgery of hernia is the most common surgical procedure performed around the world. It estimates that every year this problem affects about 20 million people including 30% of it is a abdominal hernia. Despite constant advances in surgical technique, imaging methods and the meaning of muscle biomechanics, the hernia still pose a serious challenge to physicians. The best chance of effective cure is the first repair surgery, however, postoperative hernias occur in approximately 15-20% of patients. The aim of this work is to show the problem of hernias appearing in a scar after a previously performed operation. This article contains basic information on factors that increase the risk of hernia recurrence, classification according to the recommendations of the European Hernia Society (EHS), the clinical picture and the recommended treatment for hernia.